Association between vision impairment and mortality: protocol for a systematic review and meta-analysis. Issue 6 (21st June 2020) - Ehrlich, Joshua R; Ramke, Jacqueline; Macleod, David; Swenor, Bonnielin K; Burn, Helen; Lee, Chan Ning; Waldock, William J; Zhang, Justine H; Gordon, Iris; Congdon, Nathan; Burton, Matthew; Evans, Jennifer R
Abstract : Introduction: Due to growth and ageing of the world's population, the number of individuals worldwide with vision impairment (VI) and blindness is projected to increase rapidly over the coming decades. VI and blindness are an important cause of years lived with disability. However, the association of VI and blindness with mortality, including the risk of bias in published studies and certainty of the evidence, has not been adequately studied in an up-to-date systematic review and meta-analysis. Methods and analysis: The planned systematic review and meta-analysis will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Databases, including MEDLINE Ovid, Embase Ovid and Global Health, will be searched for relevant studies. Two reviewers will then screen studies and review full texts to identify studies for inclusion. Data extraction will be performed, and for included studies, the risk of bias and certainty of the evidence will be assessed using the Grades of Recommendation, Assessment, Development and Evaluation approach. The prognostic factor in this study is visual function, which must have been measured using a standard objective ophthalmic clinical or research instrument. We will use standard criteria from WHO to categorise VI and blindness. All-cause mortality may be assessed by any method one or more years after baseline assessment of vision. Results from included studies will be meta-analysed according to relevant sections of the Meta-analysis Of Observational Studies in Epidemiology checklist. Ethics and dissemination: This review will only include published data; therefore, ethics approval will not be sought. The findings of this review and meta-analysis will be published in an open-access, peer-reviewed journal and will be included in the ongoing Lancet Global Health Commission on Global Eye Health.